Post-synthetically modified metal-porphyrin framework GaTCPP for carbon dioxide adsorption and energy storage in Li-S batteries - Király, Nikolas; Capková, Dominika; Almáši, Miroslav; Kazda, Tomáš; Čech, Ondej; Čudek, Pavel; Fedorková, Andrea Straková; Lisnichuk, Maxim; Meynen, Vera; Zeleňák, Vladimír (RSC advances, 2022)
Lithium-sulphur batteries attract increasing interest due to their high theoretical specific capacity, advantageous economy, and "eco-friendliness". In this study, a metal-organic framework (MOF) GaTCPP containing a porphyrinic base ligand was used as a conductive additive for sulphur. GaTCPP was synthesized, characterized, and post-synthetically modified by the transition metal ions (Co2+/Ni2+). The doping of GaTCPP ensured an increase in the carbon dioxide adsorption capacities, which were measured under different conditions. Post-synthetic modification of GaTCPP with Co2+/Ni2+ ions has been shown to increase carbon dioxide storage capacity from 22.8 wt% for unmodified material to 23.1 wt% and 26.5 wt% at 0 °C and 1 bar for Co2+ and Ni2+-doped analogues, respectively. As a conductive part of cathode material, MOFs displayed successful sulphur capture and encapsulation proven by stable charge/discharge cycle performances, high-capacity retention, and coulombic efficiency. The electrodes with pristine GaTCPP showed a discharge capacity of 699 mA h g-1 at 0.2C in the fiftieth cycle. However, the doping of GaTCPP by Ni2+ has a positive impact on the electrochemical properties, the capacity increased to 778 mA h g-1 in the fiftieth cycle at 0.2C.